PENGARUH KOMITMEN ORGANISASI, STRES KERJA DAN KEPUASAN KERJA TERHADAP TURNOVER INTENTION KARYAWAN PD MONGGI BUSANA INDONESIA - Marini Oktavia (Sekolah Tinggi Ilmu Ekonomi Bisnis Indonesia, 2022)
This study aims to determine the effect of organizational commitment, job stress and job satisfaction on employee turnover intention. The population in this study are employees who work at PD Monggi Busana Indonesia. The number of samples used was 92 respondents and data was collected using a questionnaire. Testing the hypothesis using multiple regression analysis which was tested using the SPSS 19 program. From the results of the research the organizational commitment variable (X1) and work stress partially have a significant effect on the level of employee turnover intention (Y), while job satisfaction has no effect on turnover intention.